Peculiarities of assessing the quality of education in physical education at the level of secondary general education - A. V. Ageev; A. M. Daurov; N. V. Makhnovskaya; S. V. Kasyanov; N. I. Sokolova (Вестник Северо-Кавказского федерального университета)
The article deals with the problem of evaluating educational results in the subject area "Physical culture". Disclosed shortcomings associated with skills ambiguity in the choice of means, methods, forms of assessment. The work notes insufficient methodological support from the standpoint of assessing educational results. An analysis of approaches to assessing the individual achievements of students, regulated by normative acts, the results of research by specialists in approbation of monitoring programs and a system for assessing the quality of physical education, and a survey of teaching staff is presented. The paper provides a theoretical justification and defines a list of recommendations aimed at improving the quality and objectivity of monitoring the assessment of educational achievements of students, obtaining comprehensive and reliable information about the state of education; conducting a systematic and comparative analysis of the educational achievements of students and making the necessary adjustments to the educational process. The mechanisms of planning and monitoring the quality of educational achievements in physical culture are determined. The indicators influencing educational results are revealed. The parameters of increasing the student's interest in the educational process are presented. A description is given of the assessment tools used for such methods as control, stimulation and diagnostics. The diagnostic parameters that should be relied upon when developing evaluation materials are determined. Effective online data collection tools are proposed to improve the quality of diagnosis, allowing flexible assessment of students' achievements. An assessment of the objectivity of control and the receipt of comprehensive and reliable information is given. As a value judgment, the directions for the implementation of self-assessment skills, self-analysis of educational achievements, which contribute to increasing motivation and motor activity, are disclosed.